Features of the application of coherent noise suppression methods in the digital holography of particles - Dyomin, Victor V.; Davydova, Alexandra Yu; Kirillov, Nikolay; Polovtsev, Igor G. (Applied sciences)
The paper studies the influence of coherent noises on the quality of images of particles reconstructed from digital holograms. Standard indicators (for example, signal-to-noise ratio) and such indicators as the boundary contrast and boundary intensity jump previously proposed by the authors are used to quantify the image quality. With the use of these parameters, for examples of some known methods of suppressing coherent noises in a holographic image (eliminating the mutual influence of virtual and real images in in-line holography, and time averaging), the features and ranges of applicability of such correction were determined. It was shown that the use of the complex field amplitude reconstruction method based on the Gerchberg–Saxton algorithm and the spatial-frequency method improves the quality of determining the particle image boundary (by boundary intensity jump) starting from the distance between a hologram and a particle, which is about twice the Rayleigh distance. In physical experiments with model particles, averaging methods were studied to suppress non-stationary coherent noises (speckles). It was also shown that averaging over three digital holograms or over three holographic images is sufficient to provide a quality of particle image boundary suitable for particle recognition. In the case of multiple scattering, when it is necessary to impose a limit on the working volume length (depth of scene) of the holographic camera, the paper provides estimates that allow selecting the optimal working volume length. The estimates were made using the example of a submersible digital holographic camera for plankton studies.